Sphere pressure: When Politics Contends with Geopolitics - Upadhyaya, Sanjay (Journal of Foreign Affairs, 2022)
Nepal’s strategic vulnerability owing to its location between two giants of Asia has risen and fallen with the status of India and China relations, the quality of their bilateral relations, and the principal external variables influencing them. In recent years, Nepal’s boisterous domestic politics has emerged as an additional source of instability. In the past, the internal fundamentals, regardless of the political system of the day, were sturdy enough to cope with often-competing pressures emanating from the north and south. The improvisation that has become the defining feature of the contemporary Nepali state, has made today’s geopolitical spasms far more ominous. While it may be outlandish to suggest that Nepal’s politics and geopolitics have become antithetical, there is sufficient basis for probing that question.